The ESP Scenario in EFL Economics Courses - Napitupulu, Selviana; Kisno, Kisno; Napitupulu, Fenty Debora (International Journal of Educational Research Excellence (IJERE), 2024)
The term "ESP" refers to a method of teaching English for any possible goal. It addresses with determining the curriculum for a scenario where students are grouped as homogeneous and have a common set of requirements. Thus, the goal of this study is to investigate the state of ESP teaching and learning in a third-year graduate student class at the University of Murni Teguh, Department of Economics. The researcher makes an effort to determine whether the ESP method of teaching EFL is used in this particular class. In order to do this, a representative sample of 50 students was selected at random and joined by their ESP instructor, a specialist in the same department. Two study tools have been used to gather data: a structured interview with the teacher and a questionnaire for the students. Consequently, a quantitative and qualitative analysis has been conducted. The findings showed that students are taught in general English with little consideration for their academic and professional demands (once they are employed). Instead, there is a strong emphasis on learning economic concepts and translating brief texts into Arabic, the students' native tongue. The ESP teacher also mentioned how he sensed a need for particular "teacher training." The findings may help ESP teachers understand what is actually required in this particular situation. Therefore, depending on the needs of each specific subject, ESP approaches should be used to teach English.